Role of DNA methylation in the development of Epstein–Barr virus‐associated gastric carcinoma1. Issue 1 (16th October 2012) - Saito, Mari; Nishikawa, Jun; Okada, Toshiyuki; Morishige, Akihiro; Sakai, Kouhei; Nakamura, Munetaka; Kiyotoki, Shu; Hamabe, Kouichi; Okamoto, Takeshi; Oga, Atsunori; Sasaki, Kohsuke; Suehiro, Yutaka; et al.
Abstract The frequencies of DNA methylation of certain tumor‐related genes are higher in Epstein–Barr virus (EBV)‐associated gastric carcinomas than in EBV‐negative gastric carcinomas. EBV‐associated gastric carcinomas have distinct clinicopathological features; however, there are no case‐control studies comparing methylation frequency between EBV‐associated gastric carcinomas and controls that have been adjusted according to the clinicopathological features of EBV‐associated gastric carcinomas. This study evaluated 25 EBV‐associated gastric carcinomas that were positive for EBV‐encoded small RNA 1 (EBER‐1) by in situ hybridization and 50 EBV‐negative gastric carcinomas that were matched with the EBV‐associated gastric carcinomas by age, sex, histology, depth of tumor invasion, and stage. Methylation status of 16 loci associated with tumor‐related genes was analyzed by methylation‐specific polymerase chain reaction (PCR) to identify genes in which DNA methylation specifically occurred in EBV‐associated gastric carcinomas. Methylation frequencies of 12 of the 16 genes were higher in EBV‐associated gastric carcinomas than in EBV‐negative controls, and the frequency of methylation of 6 specific loci (MINT2, MINT31, p14, p16, p73, and RUNX3) was significantly higher in EBV‐associated gastric carcinomas than in EBV‐negative controls. There were no significant differences in the methylation frequencies of the other genes. The mean methylation index in EBV‐associated gastric carcinomas was significantly higher than that in EBV‐negative controls. DNA methylation of tumor suppressor genes that regulate the cell cycle and apoptosis specifically occurred in EBV‐associated gastric carcinomas. Aberrant DNA methylation might lead to the development and progression of EBV‐associated gastric carcinoma. J. Med. Virol. 85:121–127, 2012. © 2012 Wiley Periodicals, Inc.